2009
DOI: 10.1007/s11434-009-0248-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and magnetic properties of near monodisperse Fe3O4 sub-microspheres

Abstract: Near monodisperse Fe 3 O 4 sub-microspheres with an average diameter of 170 nm have been synthesized by a solvothermal reduction method, using K 3 [Fe(CN) 6 ] as the raw material in the absence of any surfactants at 200℃ for 24 h. The products were detected by XRD, FESEM, TEM, and XPS. The investigation of the reaction parameters indicates that ethylene glycol plays a key role both as reducing agent and solvent. In addition, the reaction time and temperature also have important influences on the final product.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…In the absence of the hydrazine, Fe 3 O 4 could not be obtained when other conditions were kept constant. This might be because hydrazine was able to slowly oxidize Fe 2 þ ions dissociated from [Fe(CN) 6 ] 4 À to Fe 3 þ ions under hydrothermal conditions in the reaction [22]. Fe 2 þ and Fe 3 þ contributed to Fe 3 O 4 , when hydrazine was used as the oxidant.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of the hydrazine, Fe 3 O 4 could not be obtained when other conditions were kept constant. This might be because hydrazine was able to slowly oxidize Fe 2 þ ions dissociated from [Fe(CN) 6 ] 4 À to Fe 3 þ ions under hydrothermal conditions in the reaction [22]. Fe 2 þ and Fe 3 þ contributed to Fe 3 O 4 , when hydrazine was used as the oxidant.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Cai and Wan [18] have successfully synthesized Fe 3 O 4 nanoparticles in liquid polyols. Zhang et al [19] also reported the preparation of monodisperse Fe 3 O 4 sub-microspheres using ethylene glycol (EG) as both reducing agent and solvent. The advantages of polyols approach are the easily controlled experimental conditions, simplicity and less material consuming.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the presence of a detrimental surface/ crystal-structure is also related to the demagnetization effects. However, the coercivity value is higher than that of sub-microspheres (124.7 Oe) and Fe 3 O 4 nanopartiicles (274 Oe) [25,26]. These research results indicate that size and morphology may be influencing factors because the coercivity is sensitive to many structural parameters such as the internal stress, the orientation, defects and shapes.…”
Section: 1mentioning
confidence: 75%